Ost und West in der Romania: globale und regionale Vernetzungen der rumänischen Literaturen = Entre est et ouest : interconnexions globales et régionales des littératures roumaines - Constantinescu, Romanița; Dondorici, Iulia (Literaturwissenschaft, 2023)
Literary multilingualism and the transnational turn are currently hot topics in literary studies. They are best studied in the multilingual and widely networked Romanian literatures. The contributions collected here illustrate the numerous and close connections of Romanian literatures on various levels: - regionally to the languages, literatures and cultures of the Balkan region - in the European region to western and southern Romania, and - across continents, i.e. in a global context. The specific contribution that Romanian studies can make today – within Romance studies as well as in the context of current debates in literary studies – becomes apparent
Literaturangaben
"Die Aufsätze gehen auf Beiträge für die Sektion "Ost und West in der Romania. Globale und regionale Vernetzungen der rumänischen LIteraturen" des XXXVII. Romanistentages "Europa zwischen Regionalismus und Globalisierung" zurück." - Einführung
Keywords: Konferenzschrift; Literaturbeziehungen; Rumänien; Mehrsprachigkeit; Globalisierung; Literatur; Rumänisch